The relative efficiency of education and R&D expenditures in the new EU member states - Aristovnik, Aleksander (Journal of Business Economics and Management, 2012)
The paper attempts to measure relative efficiency in utilizing public education and R&D expenditures in the new EU member states in comparison to the selected EU (plus Croatia) and OECD countries. As resources allocated to education and R&D sector are significantly limited, a special emphasis should be given to their efficient use regarding the institutional and legal constraints. By applying non-parametric methodology, i.e. Data Envelopment Analysis (DEA), a relative efficiency is defined as the deviation from the efficiency frontier which represents the maximum output/outcome attainable from each input level. An analysis of (output-oriented) efficiency measures shows that among the new EU member states Hungary, Estonia and Slovenia seem to be good benchmark countries in the field of primary, secondary and tertiary education, respectively. On the other hand, Cyprus and again Hungary dominate in the field of R&D sector, even if for different reasons. The empirical results also suggest that, in general, new EU member states show relatively high efficiency in tertiary education, while lag well behind in the R&D efficiency measures.